Are Renal Cell Carcinoma with Fibromyomatous Stroma (RCC-FMS) and Thyroid-like Follicular Carcinoma of the Kidney (TLFCK) Really Independent Variants? - Stefano Stanca; Laura Boldrini; Paola Anna Erba; Pinuccia Faviana (Diagnostics, 2022)
Background: Renal cell carcinoma with fibromyomatous stroma (RCC-FMS) is a recent provisional entity already recognised in the 2016 WHO Classification of Cancer of the Urinary Tract and Male Genital Organs 4th Edition as renal cell carcinoma with (angio)leiomyomatous stroma, histologically defined as a tumour characterised by clear cells intertwined in a conspicuous vascular stroma. In the casuistry taken into consideration, another proposed variant, thyroid-like follicular carcinoma of the kidney (TLFCK), endowed with a morphology mimicking thyroid parenchyma, was examined. The aim of this work was to parse the theoretical system, experimental data and diagnostic impact of these new entities proposed in the field of renal neoplasms. Materials and Methods: An analysis of 120 cases of kidney tumours from the Department of Surgical, Medical, Molecular and Critical Area at the University of Pisa was run. Subsequently, all samples were reassessed by two pathologists with expertise in uropathology, whose revaluation provided a histomorphological study combined with subsequent and coherent immunohistochemical analyses of CK7, CD10, CAIX, CK34betaE12, CD117, vimentin, TTF-1 and thyroglobulin. These analyses were performed using the Ventana Benchmark Automated Staining System (Ventana Medical Systems, Tucson, AZ, USA) and Ventana reagents. Results: On the one hand, the data, thus brought to light, did not show an immunohistochemical profile consistent with that proposed for RCC-FMS. However, it should be emphasised that the morphological background also unearthed a poor specificity for RCC-FMS. This was specifically due to a stromal component which was, in any case, evident, although characterised by a wide range of presentation, in clear cell renal cell carcinoma (ccRCC). This latter is, indeed, the reference background for this theorised variant. On the other hand, a thyroid-like pattern was highlighted in 11 cases, more specifically in 10 ccRCCs and in one oncocytoma, presenting itself as a type of neoplastic appearance rather than as the peculiar morphological pattern of a standalone cancer. Conclusions: In the light of these results, RCC-FMS and TLFCK appear to be more appropriately variants of already categorised neoplastic entities rather than new independent neoplasias.